How to Reduce Workplace Deviant Behavior : Through Ethical Leadership and Workplace Spirituality with Organizational Commitment as Mediation - Ratu Janisa Gamasiwi; Fatmah Bagis; Endratno, Hermin; Widyaningtyas, Dian (International Journal of Scientific Research and Management (IJSRM), 2023)
A key factor in raising the caliber of human resources is education, according to expectations in order to increase development with successful (determined by educated human resources). Education is one way to improve the quality of human independence, but education will be affected because the workplace can respond negatively to factors by engaging in workplace deviant behavior. This study examines how workplace spirituality and ethical leadership can lessen workplace deviant behavior, with organizational commitment acting as a mediating factor. The research is conducted in the education sector, specifically in universities. A questionnaire is used as the data gathering tool in this qualitative study. The quota sampling method was used in this research, with 216 respondents selected from three Islamic universities in Purwokerto. The analysis in this research uses the Smart Partial Least Square (SmartPLS) application. The results of the study show that deviant behavior in the workplace is significantly and negatively impacted by workplace spirituality and ethical leadership. Furthermore, the results show that workplace deviant behavior is significantly and negatively impacted by organizational commitment. Then, some findings indicate that workplace spirituality and ethical leadership have a positive and significant impact on organizational commitment. Other findings indicate that workplace spirituality and ethical leadership have a relationship that is mediated by organizational commitment, and that workplace deviant behavior and ethical leadership are mediated by organizational commitment.